SHEIKH SALMAN DA`IM AND THE TAREKAT OF NAQSYABANDIYAH AL-KHOLIDIYAH JALALIYAH - Perangin-angin, Mawaddah (Journal of Contemporary Islam and Muslim Societies, 2022)
Abstract: The tarekat is seen as something traditional, which appears to set itself off from modern life. In reality, though, life can not ignore modernism. Consequently, there must be a connection between the roles of Sufism and modernity. The acceptance of this modernism may be seen in the ideas and principles that Sheikh Salman Da'im teaches his students. This research is qualitative and use a character research approach to analyze the thoughts and influences of a character. Data collected from library materials such as books, newspapers, articles and in-depth interviews by using open questions. The problem formulation of this research is the leadership ideals taught by Sheikh Salman Da'im in the Naqsyabandiyah al-Kholidiyah Jalaliyah Congregation, Sheikh Salman Da'im's leadership, as well as Sheikh Salman Da'im's views and actions. Based on the result of this research, Sheikh Salman Da'im is able to merge the functions of Sufism and modernity through the education he produces and the values he teaches which consist of welas asih, dono weweh, andhap asor, wicaksana, as well as his concept for social construction, and preserving religious, social, political harmony and economic development. Keywords: Sufism, Islamic values, Leadership, Sheikh Salman Da`im, Tarekat Naqsyabandiyah al-Kholidiyah Jalaliyah